The social context of reasoning Conversational inference and rational judgment. [article]. - Hilton, Denis J.
Social rules governing communication require the listener to go beyond the information given in a message, contrary to the assumption that rational people should operate only on the information explicitly given in judgment tasks. An attributional model of conversational inference is presented that shows how hearers' message interpretations are guided by their perceptions of the speaker. The model is then applied to the analysis of experiments on reasoning processes in cognitive psychology, developmental psychology, social psychology, and decision research. It is shown that the model can predict how experimental manipulations of relevant source and message attributes affect respondents' judgments. Failure to recognize the role of conversational assumptions in governing inference processes can lead rational responses to be misclassified as errors and their source misattributed to cognitive shortcomings in the decision maker. -- (from the author)